The social utility of art, 1870-1925: aestheticism and the reading public in the works of Amy Levy and Vernon Lee - Townley, Sarah R. (2008)
Traditionally, our idea of late-19th-century British Aestheticism has been understood as a socially-disengaged cultural movement. However, as Paul Tucker noted, Walter Pater suggests that aesthetic consumption can be ethically-engaged when informed by a 'scholarly conscience.' The following study is concerned with writers Amy Levy (1861-1889) and Vernon Lee (1856-1935), whose dissatisfaction with the social elitism of the Paterian critic and interest in the public sphere, prompted a re-theorisation of the relationship between art's aesthetic value and its social utility. Surveying the breadth of each writer's critical and fictional works, I argue that whilst Levy and Lee extend Aestheticism to a broader reading public, the term 'public' is something of a misnomer. Their oeuvres are not, in principle, open to anyone. Both well-educated writers, Lee and Levy do not forfeit their intellectual integrity and creative esteem; instead, both mediate between aesthetic perfectionism and social utility.